2012
DOI: 10.1177/0731684412458333
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-assisted melt compounding of polypropylene/carbon black composites: Processability, filler dispersion and mechanical properties

Abstract: Composites of polypropylene and carbon black were melt compounded by a vibration-assisted process. For comparison, conventional extrusion was also used for preparation of the same composites. A throughput of the vibration-assisted process was established to be higher than that of conventional extrusion. Microscopic images of the extrudates demonstrated better dispersion of the fillers when the vibration force field was applied. The mechanical properties and viscoelastic behavior of the composites were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Composites, based on polymer foils containing dispersed ceramic particles are promising materials with desired thermal properties depending on filler amount and microstructure [1][2][3][4][5][6][7][8]. Despite of the large number of investigations and physical models, giving the dependence of thermal properties on filler amount, some aspects of the preparation -properties relationship of such composites remain unexplained.…”
Section: Introductionmentioning
confidence: 99%
“…Composites, based on polymer foils containing dispersed ceramic particles are promising materials with desired thermal properties depending on filler amount and microstructure [1][2][3][4][5][6][7][8]. Despite of the large number of investigations and physical models, giving the dependence of thermal properties on filler amount, some aspects of the preparation -properties relationship of such composites remain unexplained.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Results show that the effects of process settings, materials, and machine structure have great influence on pressure development, and the stable pressure is highly important to the maintenance of the process stability. However, the melt viscosity reduced 19,20 the mixing performance and mechanical properties 21,22 and improved with the introduction of regular vibration forces during extrusion. Recent research results have shown that vane extruder (VE) composed of several vane plasticizing conveying units 23 is based on the positive displacement conveying mechanism dominated by extensional deformation, which has many advantages such as stable output, better dispersive, and distributive mixing, reduced melt temperature, wide adaptability.…”
Section: Introductionmentioning
confidence: 99%
“…New and even more powerful capabilities are rapidly becoming available. Recently, the excitation technique has been applied in polymer processing and has gained more and more interest [2][3][4][5][6][7][8][9][10][11]. The types of external excitation include sonic, ultrasonic, electromagnetic, radiation and mechanical vibration depending on their origins.…”
Section: Introductionmentioning
confidence: 99%